The teaching attitude and the implementation of projects of educational innovation, in the public educational institutions of the district of Tacna, year 2014 - Pintado Caipa, Elena (2018)
Objective: to demonstrate the influence of the teaching attitude in the implementation of educational innovation projects, in the public educational institutions of the district of Tacna, in 2014. Methodology: the research is of Basic or Pure Type, with explanatory causal descriptive design. The sample consisted of a total of 107 teachers who participated in educational innovation projects, to which a Likert scale was applied to measure the teaching attitude and a questionnaire to measure the level of implementation of educational innovation projects. Result: the predominant teaching attitude among teachers in the district of Tacna who participate in educational innovation projects, is the indifferent attitude, with 72.9%, a significant percentage, 13.1% representing teachers with a positive attitude, and 14.0% who represents teachers with a negative attitude. The level of implementation of educational innovation projects, in the district of Tacna is 37.4% in a regular level of implementation, 33.6% of projects in a good level of implementation, 14% of projects in an excellent level of implementation, and 15% at a low level of implementation. Conclusion: it can be affirmed that the predominant teaching attitude prevalent in the teachers participating in the educational innovation projects, in the district of Tacna, in 2014, has a significant influence on the level of regular implementation of educational innovation projects.